COMPARATIVE PERFORMANCE OF THREE PROBIOTIC ISOLATES OF Lactobacillus sp. ISOLATED FROM DAIRY PRODUCTS (Applied Biological Research, 2024)
The probiotics, when administered in adequate amounts, have the ability to  confer health benefits to the host by positively influencing the composition and  function of gut microbiota. The present study was aimed to isolate and  characterize the probiotic bacteria from locally available curd and Yakult  samples and compare them with Sporolac for probiotic properties. Three  bacterial isolates were isolated and tentatively identified on morpho-cultural and  biochemical characteristics as Lactobacillus sp. The isolates were named  Lactobacillus sp. isolates PBC, PBY and SPO. E coli was used as negative control.  The study revealed that the isolates exhibited auto-aggregation and co aggregation activities, more in isolate SPO as compared to the isolates PBC and  PBY. Biofilm and quorum quenching activities were high in Lactobacillus sp. isolate PBC and PBY as compared to Lactobacillus sp. isolate SPO. The other  tests showed more or less similar properties as compared to the commercially  available product. The study revealed that the probiotic bacterial isolates from  curd and Yakult had more beneficial properties than the commercially  processed probiotic bacteria.
Keywords: Auto-aggregation; biofilm; Lactobacillus; MATH test,; probiotics